Unraveling the TEC-associated landscape in hepatocellular carcinoma: a comprehensive study based on multi-omics analyses - Jianwei Lan; Longhui Xie; Dekun Song; Pengpeng Liu; Quanyan Liu (Discover Oncology)
Abstract The tumor microenvironment (TME) plays a pivotal role in tumor progression, immune evasion, and therapeutic responses. Among its key components, endothelial cells (ECs) are crucial regulators of angiogenesis, immune cell trafficking, and metabolic adaptations. This study integrates single-cell and transcriptomic analyses to identify tumor-specific endothelial cell signatures in hepatocellular carcinoma (HCC) and stratify tumors into three distinct molecular subtypes. These subtypes exhibit unique immune landscapes and biological characteristics, including pathway activation and differential responses to immunotherapy and targeted treatments. Using machine learning, we developed a robust prognostic scoring model to predict patient outcomes and therapy responsiveness, which was validated across independent cohorts. Our findings highlight the critical role of endothelial cells in modulating the TME and underscore the potential of targeting EC-specific molecular features to enhance the efficacy of immunotherapy and optimize personalized cancer treatment.